Cultural adaptation and validation of the Kidney Disease and Quality of Life-Short Form (KDQOL-SF™) version 1.3 questionnaire in Uganda - Bagasha, Peace; Naitala, Ronald; Namukwaya, Elizabeth; Leng, Mhoira; Katabira, Elly; Namisango, Eve (African Journal of Nephrology, 2022)
Background: Chronic kidney disease is on the rise in sub-Saharan African countries such as Uganda, and patients often present with advanced disease requiring kidney replacement therapies. Health-related quality of life is a key outcome in chronic kidney disease management but, in Uganda, no tools have been validated to measure this. The aim of this study was to culturally adapt and validate the Kidney Disease Quality of Life-Short Form version 1.3 (KDQOL-SF™) questionnaire for use in the Ugandan setting. Methods: We conducted a four-phase, mixed-methods study which included translation, cultural adaptation, optimisation of face validity and field testing. Our participants included healthcare workers, and patients aged 18 years with an estimated glomerular filtration rate <15 mL/min/1.73 m2. Results: The tool was culturally adapted and translated into one of the Ugandan languages, Luganda, which, with an English version of the tool, was validated and field tested. Over 80% of the subdomains had less than 10% floor and ceiling effects. For reliability, Cronbach’s α coefficient scores ranged from 0.96 to 0.41, with 10 out of 18 subdomains scoring >0.70, indicating acceptable internal consistency. The tool demonstrated discriminant validity, with patients with comorbidities reporting lower quality of life scores, as postulated. Conclusions: The Luganda and English versions of the KDQOL-SF questionnaire have sufficient face and content validity, reliability and acceptability to assess the quality of life of patients with kidney failure in Uganda.